2007
DOI: 10.1007/s11103-007-9153-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the ADP-glucose pyrophosphorylase isoforms essential for starch synthesis in the leaf and seed endosperm of rice (Oryza sativa L.)

Abstract: ADP-glucose pyrophosphorylase (AGP) catalyzes the first committed step of starch biosynthesis in higher plants. To identify AGP isoforms essential for this biosynthetic process in sink and source tissues of rice plants, we analyzed the rice AGP gene family which consists of two genes, OsAGPS1 and OsAGPS2, encoding small subunits (SSU) and four genes, OsAGPL1, OsAGPL2, OsAGPL3 and OsAGPL4, encoding large subunits (LSU) of this enzyme heterotetrameric complex. Subcellular localization studies using green fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
160
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 82 publications
8
160
0
1
Order By: Relevance
“…Confirmation of this result for AGPLLZM and AGPSLZM is provided by a proteomics study in which both proteins were identified directly in isolated maize leaf plastids (Majeran et al, 2005). Further support comes from a proteomics analysis that identified the orthologs of AGPSLZM and AGPLEMZM in wheat amyloplasts (Balmer et al, 2006) and by fluorescence localization of GFP fusions to the AGPase SS and LS orthologs of rice (Lee et al, 2007). …”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Confirmation of this result for AGPLLZM and AGPSLZM is provided by a proteomics study in which both proteins were identified directly in isolated maize leaf plastids (Majeran et al, 2005). Further support comes from a proteomics analysis that identified the orthologs of AGPSLZM and AGPLEMZM in wheat amyloplasts (Balmer et al, 2006) and by fluorescence localization of GFP fusions to the AGPase SS and LS orthologs of rice (Lee et al, 2007). …”
mentioning
confidence: 83%
“…Type 1 genes generate two different transcripts referred to as type 1a and type 1b (Thorbjornsen et al, 1996;Burton et al, 2002;Ohdan et al, 2005). Type 1a transcripts encode a cytosolic protein that was directly identified as the extraplastidial AGPase SS from endosperm (Burton et al, 2002;Johnson et al, 2003;Lee et al, 2007). Type 1b transcript accumulates in endosperm and is predicted to encode a plastidial protein, but the AGPase SS purified from wheat or barley amyloplasts did not match the amino acid sequence predicted by this mRNA (Burton et al, 2002;Johnson et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The large subunit (L1) and small subunit (S1 and S2a) of AGPase protein in rice crop (cv. Dongjin) has been localized in plastid organelles, while S2b small subunit protein locates in cytosol (Lee et al 2007). Also, the sensitivity and function of those subunits of AGPase protein relating to salt stress are still undiscovered.…”
Section: Expression Levels Of Starch Involving Genes Under Salt Stressmentioning
confidence: 99%
“…The chloroplast organelle, especially in the endosperm of cereals, is the origin of starch biosynthesis, forming complex polysaccharides, including linear and branched molecules of glucose polymer, amylose and amylopectin, by ADP-glucose pyrophosphorylase (ADP-AGPase), starch synthase (SS) and starch branching enzymes (SBE). In starch synthesis, ADP-glucose derived from photosynthesis is synthesised by the action of ADP-GPPase, which is the case in rice (Ballicora et al 2004;Lee et al 2007). The elongation of starch proceeds via SS activity that catalyses the transfer of glycosyl moiety of ADP-glucose to the non-reducing end of pre-existing α-D-1,4-glucan primer.…”
Section: Introductionmentioning
confidence: 99%